Effect of Earthworm on Wound Healing: A Systematic Review and Meta-Analysis - Wang, Dong; Ruan, Zhen; Zhang, Rongchao; Wang, Xuejing; Wang, Ruihui; Tang, Zhishu (Frontiers in Pharmacology, 2021)
Background: Earthworm, also called dilong (Chinese language), has been used as a traditional Chinese medicine for thousands of years. Recently, some scientists believe that earthworm extracts (EE) can promote wound healing. However, its effectiveness remains controversial. We conducted a meta-analysis to evaluate the effect of EE on wound healing based on the healing rate. Methods: We comprehensively reviewed literature that mentioned EE for wound healing in the PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), VIP database for Chinese Technical Periodicals, and WanFang database that have been published until January 2021. We computed weighted mean difference (WMD) for analysis with RevMan 5.3 software in animal and human models groups. Two researchers independently selected studies and evaluated the risk of bias with the Cochrane Collaboration tool. The quality of the evidence was assessed with the Cochrane risk of bias tool. This study is registered on PROSPERO (CRD42020168400). Results: From 2,486 articles, we selected 16 studies for analysis. EE treatment was associated with improvements in wound healing performance based on wound healing rate (mouse model: weighted mean difference (WMD) = 3.55, 95% confidence interval (CI): 2.34–4.77, p < 0.00001; rat model: WMD = 17.29, 95% CI: 5.75–28.82, p = 0.003; rabbit model: WMD = 19.29, 95% CI: 9.95–28.64, p < 0.0001). Clinical studies also confirmed that EE could reduce healing time in hospital (WMD = −8.94, 95% CI: −17.75 to −0.14, p = 0.05). Conclusion: The results of this meta-analysis demonstrated the efficacy of EE on wound healing process. As a corollary, EE can be a useful natural product for wound healing drug development. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=168400, identifier CRD42020168400.